2021
DOI: 10.47577/tssj.v17i1.2866
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Emotional Intelligence and Parenting Styles on Self-Esteem in a Sample of Respondents in Nigeria

Abstract: Studies consistently suggest that emotional intelligence and parenting styles are associated with self-esteem, although validation has relatively been based on correlation analysis. Using a sample of 252 respondents in Nigeria, the present study examined the relationships among parenting styles, emotional intelligence, and self-esteem with the aim of generating knowledge that transcends the nature and extent of their correlations. A bivariate analysis identified significant correlations: emotional intelligence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…The result of this study revealed that the majority of the participants reported their father and mother parenting style as authoritative style, which was consistent with a study done in Karnataka on adolescents(17). Also, the result from the study revealed that permissive parenting style of both parents was negatively associated with emotional quotient, which was in accordance with the previous study results (28,29). This result was in accordance with the work of Alegre which found out the permissive parenting or low demand and high responsiveness was negatively related with the emotional intelligence(30) and authoritative style of parenting was positively related with emotional intelligence.…”
Section: Discussionsupporting
confidence: 92%
“…The result of this study revealed that the majority of the participants reported their father and mother parenting style as authoritative style, which was consistent with a study done in Karnataka on adolescents(17). Also, the result from the study revealed that permissive parenting style of both parents was negatively associated with emotional quotient, which was in accordance with the previous study results (28,29). This result was in accordance with the work of Alegre which found out the permissive parenting or low demand and high responsiveness was negatively related with the emotional intelligence(30) and authoritative style of parenting was positively related with emotional intelligence.…”
Section: Discussionsupporting
confidence: 92%
“…The importance of emotional regulation is shown both in the field of parenting and its implications on an effective parent-child relationship [47], but also in obtaining well-being. This research makes empirical contributions demonstrating the interdependence between the three variables: emotional regulation, optimism, and parenting style.…”
Section: Discussionmentioning
confidence: 99%